Body composition changes with testosterone replacement therapy following spinal cord injury and aging: A mini review. (2nd November 2018) - Nightingale, Tom E.; Moore, Pamela; Harman, Joshua; Khalil, Refka; Gill, Ranjodh S.; Castillo, Teodoro; Adler, Robert A.; Gorgey, Ashraf S.
Abstract : Context: Hypogonadism is a male clinical condition in which the body does not produce enough testosterone. Testosterone plays a key role in maintaining body composition, bone mineral density, sexual function, mood, erythropoiesis, cognition and quality of life. Hypogonadism can occur due to several underlying pathologies during aging and in men with physical disabilities, such as spinal cord injury (SCI). This condition is often under diagnosed and as a result, symptoms undertreated. Methods: In this mini-review, we propose that testosterone replacement therapy (TRT) may be a viable strategy to improve lean body mass (LBM) and fat mass (FM) in men with SCI. Evidence Synthesis: Supplementing the limited data from SCI cohorts with consistent findings from studies in non-disabled aging men, we present evidence that, relative to placebo, transdermal TRT can increase LBM and reduce FM over 3–36 months. The impact of TRT on bone mineral density and metabolism is also discussed, with particular relevance for persons with SCI. Moreover, the risks of TRT remain controversial and pertinent safety considerations related to transdermal administration are outlined. Conclusion: Further research is necessary to help develop clinical guidelines for the specific dose and duration of TRT in persons with SCI. Therefore, we call for more high-quality randomized controlled trials to examine the efficacy and safety of TRT in this population, which experiences an increased risk of cardiometabolic diseases as a result of deleterious body composition changes after injury.